Karakterisasi Proses Pembuatan Simplisia Daun Sirih Hijau (Piper Betle) Sebagai Sediaan Obat Penyembuhan Luka - paskalis trianus kiko; Wintari Taurina; Mohamad Andrie (Indonesian Journal of Pharmaceutical Education, 2023)
Green betel leaf (Piper betle) is used in the manufacture of wound healing preparations, has a function as an antiseptic and eugenol that can kill bacteria. This study aims to characterize the process of making simplicia and simplicia green betel leaf (Piper betle L.) obtained at Jalan Parit Demang, Gg. Kulang Leather, Parit Tokaya No. 6, South Pontianak District, Pontinanak City, West Kalimantan 78121 which is used as raw material for wound healing drug preparations. Green betel leaf simplicia was characterized biologically including habitat, morphology, physically including organoleptic, microscopic, water content, ash content, and acid insoluble ash content, as well as chemically namely phytochemical screening. This characterization is also carried out in the process of making simplicia picking, wet sorting, packing, washing, dry sorting, making simplicia, packaging, and storage. The yield of simplicia was 23.27%. The results of the characterization of green betel leaf are at an altitude of 200-1000 m above sea stage which has a rainfall of 2250-4750 mm in keeping with year. Heart-fashioned leaves, sleek leaf surface, pointed with a leaf period of 6-17.5 cm and a width of 3.5-10 cm.betle leaves have a distinctive aroma, taste slightly spicy, and greenish brown in color. The water content, ash content, acid insoluble ash content and total phenol in green betel leaf simplicia were 12.8%, 7.04%, 3.13%, phenol content 760 nm, absorbance 0.0520 and obtained levels of 23.3379 ppm. Positive for alkaloids, flavonoids, saponins, triterpenoids, tannins.